Role of hydrogen-enrichment for in-direct diesel engine behaviours fuelled with the diesel-waste biodiesel blends - Alcelik, Necdet; Saridemir, Suat; Polat, Fikret; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Carbon footprint indicates the total amount of greenhouse gases released into the atmosphere by individuals, institutions and countries. The widespread use of fossil fuels is a big player which increases the carbon footprint. Therefore, switching to sustainable alternatives in energy production and consumption is an effective step in combating climate change, as well as efforts to prevent the depletion of fossil fuels. In this regard, although biodiesels offer a solution to the depletion of fossil fuels, with this advantage, the effects of production processes and use on environmental sustainability should be taken into consideration. Many scientific studies have shown that engine performance remains below standards with biodiesel. The availability of hydrogen as an energy carrier in cylinder to overcome the above -mentioned negative situations has recently become a popular topic for fuel researchers. In this work, the diesel-biodiesel fuels were blended proportionally and tested on a threecylinder water-cooled in -direct diesel engine at varying loads (15, 30, 45, and 60 Nm) and a constant engine speed of 2200 rpm for observing the effects of test fuels on combustion, performance, and emissions characteristics of diesel engine. First of all, conventional diesel fuel (D) was used to obtain reference data, and then B20 fuel obtained by mixing waste cooking oil with 20 % by volume of diesel fuel was used. The remaining 4 fuels are test fuels obtained by giving hydrogen from the intake manifold at different flow rates (10, 20, 30, and 40 L/min) in addition to B20 fuel. These fuels are called B20 + 10 Lpm H 2 , B20 + 20 Lpm H 2 , B20 + 30 Lpm H 2 and B20 + 40 Lpm H 2 , respectively. As a result, the BSFC of B20 fuel increased by 8.78 % compared to diesel fuel, and then the addition of hydrogen dropped the BSFC value by 8.8 %, 13.02 %, 17.16 %, and 22.12 % for B20 + 10 Lpm H 2 , B20 + 20 Lpm H 2 , B20 + 30 Lpm H 2 , and B20 + 40 Lpm H 2 , respectively. Hydrogen enrichment also had a positive impact on BTE. Although the BTE dropped by 6.14 % in B20 fuel compared to diesel, it increased by 4.51 %, 5.05 %, 5.62 %, and 7.12 % in B20 + 10 Lpm H 2 , B20 + 20 Lpm H 2 , B20 + 30 Lpm H 2 and B20 + 40 Lpm H 2 fuels, respectively. The addition of 10, 20, 30, and 40 Lpm H 2 to B20 fuel reduced NOx emissions by 31.25 %, 33.08 %, 38.87 %, and 41.46 %, respectively, and also reduced CO emissions by 17.47 %, 30.73 %, 51.8 % and 59.04 % respectively.
Keywords: Hydrogen enrichment; Combustion; Engine performance; Environmental impacts; COMPRESSION-IGNITION ENGINE; DUAL-FUEL; COMBUSTION CHARACTERISTICS; EMISSION CHARACTERISTICS; EXHAUST EMISSIONS; PORT INJECTION; COOKING OIL; INTAKE AIR; PERFORMANCE; GAS; Thermodynamics; Energy & Fuels